2009
DOI: 10.1016/j.brainres.2009.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of endothelial nitric oxide synthase following pressure-induced insult to the optic nerve

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. In this paper we use the pig optic nerve, a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The specificity of the nNOS antisera used in this study was previously established with Western blots (Giove et al, 2009). The specificity of the monoclonal antisera directed against eNOS has been characterized in retina by using both immunocytochemistry and Western blots (Balaratnasingam et al, 2009). The characteristic labeling in horizontal cells seen with the calbindin antisera and the labeling of rod bipolar cells seen with the PKCa antisera was identical to that previously described for the C57/Bl6J mouse retina (Haverkamp and Wassle, 2000).…”
Section: Antisera Characterizationmentioning
confidence: 99%
“…The specificity of the nNOS antisera used in this study was previously established with Western blots (Giove et al, 2009). The specificity of the monoclonal antisera directed against eNOS has been characterized in retina by using both immunocytochemistry and Western blots (Balaratnasingam et al, 2009). The characteristic labeling in horizontal cells seen with the calbindin antisera and the labeling of rod bipolar cells seen with the PKCa antisera was identical to that previously described for the C57/Bl6J mouse retina (Haverkamp and Wassle, 2000).…”
Section: Antisera Characterizationmentioning
confidence: 99%
“…T he human optic nerve head (ONH) is composed of approximately 1.2 million retinal ganglion cell (RGC) axons and is one of the most metabolically active sites in the central nervous system. 1 The energy demands of RGC axons along the course of the ONH are not uniform as evidenced by the marked variation in mitochondrial enzymes, 2 cytoskeletal proteins, [3][4][5] myelin proteins, 6,7 astrocytes, 8,9 and nitric oxide synthase systems 10 between laminar regions. The highly compartmentalized nature of RGCs 11 and the marked heterogeneity in energy supply/demand relationships between laminar compartments are proposed to be an important reason why certain sites within the ONH are more vulnerable to injury and disease than others.…”
mentioning
confidence: 99%
“…2,3 In vivo optic nerve measurements performed in our laboratory and other centers have demonstrated the presence of a significant pressure gradient at the lamina cribrosa, which is consequent to the decrease in tissue pressures between prelaminar and retrolaminar regions of the optic nerve head. 4 -7 Previous reports, together with histologic studies also performed in our laboratory, have revealed important correlations between the change in translaminar tissue pressure and the distribution of neuronal cytoskeleton proteins, 8 mitochondria, 9,10 nitric oxide synthase enzymes, 11 and axonal transport processes, [12][13][14] suggesting that optic nerve tissue is cyto-architecturally adapted to the laminar environment. It is unknown if anatomical and physiological variations within the human optic nerve head have a similar influence on regional CRA and CRV endothelial characteristics; however, this knowledge would be useful for improving our understanding of pathogenic mechanisms underlying ocular vascular diseases.…”
mentioning
confidence: 99%